Discussing Affirmative Actions in Higher Education Institutions in Santa Catarina: Between Discourses and Institutional Policies - Pimenta, Renata Waleska de Sousa (2025)
In recent years, research on affirmative actions in higher education institutions has grown, seeking to understand its effects on student development and on the transformation of institutional culture, influenced by the presence of students from different racial, economic, and sociocultural backgrounds. This study aims to analyze the management strategies of affirmative actions in federal public higher education institutions in Santa Catarina. The specific objectives include mapping the institutions in the state and identifying the strategies adopted to manage these policies. The research uses a qualitative approach and a discursive analysis of information available on institutional websites and documents. The results indicate that the institutions present heterogeneous realities, with significant variations in their commitment to affirmative action policies. Although there has been some progress, the management of these policies still faces challenges, requiring a deeper analysis of the power relations implicit in institutional practices to promote effective changes.